The Effectiveness of the Financial Services Authority Supervisory Board in Supervising the Board of Commissioners - Suwinto Johan; Ariawan Gunadi (Universitas Negeri Semarang, 2024)
Undang Undang Pengembangan dan Penguatan Sektor Jasa Keuangan or the Law of Financial Services Sector's Development and Reinforcement has granted an absolute authority for Otoritas Jasa Keuangan (OJK) or Financial Services Authority to file for bankruptcy and postpone debt payment obligations (PKPU) against financial services institutions. OJK is led by a board of Commissioners consisting of 11 members whose authority requires supervision from a capable institution. To address this, the P2SK law established the OJK Supervisory Board responsible for overseeing the authority. Yet, OJK SB limitedly assists the House of Representatives in supervising the OJK without having any direct authority to give sanctions or indirect authority over the OJK Commissioners. Therefore, the SB OJK needs to be granted authority such as in the Limited Liability Company Act. Interviews should be conducted to business actors to explore this issue in the future studies.